The Ngoma Consciousness: IsiNgqi neSandi as existing and accessible tools for healing and therapy in Africa - Koela, Nkosenathi (Centre for Theatre, Dance and Performance Studies, 2025)
This thesis explores the ritual archive of isingqi (energy, rhythm and vibration) used in Ngoma (the divination arts and ecology) through ingoma (traditional sound and chants) as accessible tools for healing and therapy. Ngoma, etymologically, is a proto-Bantu term for an African praxis within which exists an ecology of related institutions such as the practice of medicine, divination, crafts, music, and ritual. Central in this thesis is the systemic dispossession and destruction of indigene ecologies of healing in South Africa as a result of coloniality, which De Sousa Santos (2015) unpacks through the framework of epistimicide and I unpack through the framework of ecolocide and musicolocide. The central question this thesis seeks to answer is: How is ritual involving isingqi used and preserved in the divination arts of/through ingoma (traditional sound and chants)? The overall objective is to unpack and explore this African (Ngoma) philosophical praxis and its related ecology of knowledge, through the applied method of ritual music as vibrations of healing in Southern Africa, and to offer an informed and decolonial use of ritual technologies such as ingoma and isingqi. To do this, I draw from inter-disciplinary research and archival literature that explores various epistemologies and uses of sound in African indigene communities. I also use the existing ritual archive of Ngoma and its modalities through a co-operative co-design method. The practical elements of my research provide a repository within which to explore some of the possibilities of Ngoma as consciousness, an ecology of divination arts, and praxis in the current context. This thesis argues that African indigenous scholars must engage deeply with African epistemologies like Ngoma to develop authentic technologies and healing modalities that can enrich South Africa's cultural and healing ecology. Doing so may help reinstate African- conscious institutions of healing in various sectors of society and introduce hybrid forms of sound therapy and psychosomatic treatments, involving unique healing methods through Ngoma rhythmic manipulation. My findings argue for a clear distinction between performance studies and indigene ritual studies. This distinction can provide a platform for interdisciplinary models of scholarship that enrich indigene knowledge systems and encourage research into African healing praxes.